Audit Committee Characteristics and Audit Delay among Nigerian Oil and Gas Companies - Ojali, Jemila Sheidu; Adamu, Idris Adamu; Shawai, Aliyu Sani (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2023)
This study examines the effect of audit committee diversity on audit delay of listed oil and gas companies in Nigeria. The study utilized a sample of 6 oil and gas companies for the period of 2011 to 2020 listed from Nigerian Exchange Group (NGX) market. A random effects regression has been employed in this study. Results from the study revealed that female directors in audit committee with financial expertise and presence of independent directors on audit committee have a negative and statistically significant effect on audit delay of listed oil and gas companies. Therefore, this study can be used by the policy makers or regulators in formulating policies on independent directors and women directors on board in Nigeria.